New statistical formulations for determination of qualification test plans of safety instrumented systems (SIS) subject to low/high operational demands - Khalil, Y.F. (Reliability engineering & system safety, 2019)
•Provided a framework for reliability qualification of safety instrumented systems.•Developed statistical formulations to design reliability demonstration test plans.•Quantified impact of confidence level on reliability test duration and sample size.•Quantified impact of shape parameter β on reliability test duration and sample size.•Quantified impact of operational modes on reliability test duration and sample size. This paper aims to develop new statistical formulations to design efficient reliability demonstration test (RDT) plans for electrical/electronic and programmable electronic (E/E/ES) safety instrumented systems (SIS) subject to requirements of IEC 61508-1 (2010) standard.11IEC 61508-1:2010. Functional safety of electrical/electronic/programmable electronic (E/E/ES) safety-related systems. Source: http://www.iec.ch/functionalsafety/standards/ A case study is presented to show how the proposed statistical formulations can be employed to design RDT plans to validate whether SIS target mission reliability (TMR) can be met under a specified confidence level. Discussions includes trade-offs between test duration and number of units on test and sensitivity studies showing how the demonstrated reliability at end of mission life is impacted by SIS operational mode and key statistical parameters. The major contributions that this research offers are: (i) A framework to guide reliability practitioners in applying the proposed statistical formulations to design optimum RDT plans and articulate mission reliability statements (MRS) to support regulatory certification of new SIS designs. (ii) A methodology, demonstrated by a practical case study, to show how RDT plans can be designed to meet targets set by the applicable standards. The developed framework is robust and can support certification of safety systems in a wide variety of industrial applications.